2010
DOI: 10.1007/s00417-010-1509-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of optical low-coherence reflectometry and applanation ultrasound biometry on intraocular lens power calculation

Abstract: Based on excellent repeatability of the Lenstar and acceptable repeatability of applanation ultrasound, two techniques may be used interchangeably. The predicted refractive error of ± 0.20 D in 95% of the observations has never been achieved. Optical low-coherence reflectometry might become a new standard method for biometric measurement needed for intraocular lens-power calculation in patients with cataract.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 28 publications
1
18
0
Order By: Relevance
“…Therefore, our results demonstrate that there is very good intraobserver reliability, in agreement with previous reports. 7,10,11 The mean difference in AL measurements between dilated and undilated pupils was 20.04 ± 0.23 mm, which means that dilating the pupil does not adversely affect the measurement of AL (P = 0.313).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Therefore, our results demonstrate that there is very good intraobserver reliability, in agreement with previous reports. 7,10,11 The mean difference in AL measurements between dilated and undilated pupils was 20.04 ± 0.23 mm, which means that dilating the pupil does not adversely affect the measurement of AL (P = 0.313).…”
Section: Discussionmentioning
confidence: 93%
“…It offers a contact-free method to assess the AL and has higher resolution and precision in measuring IOLs. 1,2,[5][6][7] However, when performing biometry with the Lenstar LS 900, patients with certain types of cataracts may pose difficulties. 4 Dilating the pupil may solve this type of problem; however, it is unknown whether pupil dilation affects the parameters.…”
mentioning
confidence: 99%
“…The PEX group and the control group were further divided into two subgroups: emmetropes and hypermetropes. LENSTAR LS 900® was used to measure ocular optical components [3][4][5][6][7][8][9]: axial length (AL), central corneal thickness (CCT), anterior chamber depth (ACD), lens thickness (LT), retinal thickness (RT), keratometry values (keratometry of the steepest meridian (K1), keratometry of the flattest meridian (K2), its position regarding horizontal line (AXIS) and the difference between K1 and K2 (astigmatism, AST)), horizontal irideal diameter (WTW) and pupillary diameter (PD). Ethics committee approval of University Hospital "Sveti Duh", Zagreb, Croatia, was secured for the study reported.…”
Section: Methodsmentioning
confidence: 99%
“…Optical low-coherence reflectometry (OLCR) biometer LENSTAR LS 900® is the newest generation of optical biometer [3][4][5][6][7][8][9]. It provides true A-scan measurements of eight optical ocular components in a single shot without contacting the eye [3][4][5][6][7][8][9] (Fig. 2).…”
Section: Introductionmentioning
confidence: 99%
“…Optical biometry has been shown to yield extremely accurate and reliable axial length measurements, and measurements obtained with these two methods agree closely and are interchangeable [1923]. …”
Section: Discussionmentioning
confidence: 99%